Article Efforts to Preserve Traditional Madurese Performing Arts by Akhmad Darus in Sumenep Regency: Narratives of a Madurese Artist in Safeguarding Local Performing Arts Heritage - Anhar, Syadilah Istighfarini; Wahyuni Rahayu, Eko (Solah, 2026)
This research aims to describe the efforts made by Akhmad Darus in preserving traditional Madurese performing arts in Sumenep Regency. Using qualitative research methods with an ethnographic approach, data was collected through in-depth interviews and field observations. The results show that Akhmad Darus has made significant contributions to the preservation of Madurese traditional performing arts through various efforts including: (1) establishing the Teng Tinkerbell Arts Development Center as a learning platform, (2) reviving extinct traditional dances such as guplang, sikro, thengtere', rateb, and ngo'o dances, (3) creating new works that maintain traditional characteristics, (4) actively participating in competitions and performances at local, regional and national levels, and (5) conducting coaching activities in various villages. These efforts have succeeded in maintaining the existence and sustainability of Madurese traditional performing arts, especially topeng dance, gamelan music, macapat songs, and traditional dances in Sumenep Regency.